Experiences and perceptions of social constraints and social change among lesbian, gay, bisexual and transgender persons in Lesotho. Issue 5 (4th May 2019) - Logie, Carmen H.; Alschech, Jonathan; Guta, Adrian; Ghabrial, Monica A.; Mothopeng, Tampose; Ranotsi, Amelia; Baral, Stefan D.
Abstract: Lesbian, gay, bisexual, transgender and other sexually and gender diverse persons negotiate for their identities, create communities and advocate for their rights throughout the world. However, there are limited data about the perceptions of social change among sexually and gender diverse persons in contexts where same-sex sexual practices have been recently decriminalised, such as in 2010 in Lesotho. We conducted semi-structured in-depth interviews with sexually and gender diverse persons ( n = 46) and six key informants. Findings were analysed using Social Worlds Theory. Participants discussed social constraints and marginalisation across structural (legal systems, employment, education), community (beliefs that sexual and gender diversity are incongruent with Basotho culture; stigma), and familial (tensions with religion and cultural gendered economic traditions) dimensions. The narratives also revealed perceived change across structural (changing norms in legal, employment and education spheres), community (larger community and LGBT community change), familial (negotiating acceptance), and internal (active resistance) domains. The findings reported here can inform multi-faceted programmes to challenge stigma, violence and gender inequity; build social capital; and address the health and human rights priorities of sexually and gender diverse persons in Lesotho.